THE AESTHETICS OF MISERY: AN INTERPRETATION AND COMPARATION IN CONTEMPORARY INTERIOR DESIGN - Jamaludin Jamaludin; Anwar Subkiman (Jurnal Sosioteknologi, 2018)
This paper discusses symbolic interior design and contemporary which are relevant to the experimental work called Aesthetics of Misery presented at the Milan Furniture Fair in April 2015. The exhibition presented sixteen works by students of the Interior Design Postgraduate Program at Politechnico di Milano Italia. This new approach to design was launched by Andrea Branzi and Michele de Lucchi, the two main designers at Milan. Viewed from aesthetics, the works on display have symbolic aesthetic elements. The works display a "social environment" based on the concept of suffering. Descriptive analysis method is used to explain the background and aesthetic goals of suffering. Observation in contemporary interior design is used as an interpretation of this concept as well as a comparative study. The aim is to find an implementation that what Andre Branzi and Michele de Lucchi call an aesthetic of suffering in various approaches and design styles, already in contemporary interior design work. The results showed that in an indirect form, the concept of misery in various approaches and design styles is existed or represented in industrial-style interior design work which in addition to using old factory-nuanced materials, symbolically showed the element of suffering. Keywords:  ABSTRAK Paper ini membahas karya eksperimental yang disebut Aesthetics of Misery (Estetika Penderitaan) yang dipresentasikan di Milan Furniture Fair pada bulan April 2015. Pameran ini menampilkan enam belas karya mahasiswa Program Pascasarjana Desain Interior Politechnico di Milano Italia yang digagas oleh Andrea Branzi dan Michele de Lucchi, dua desainer utama di Milan. Selain membahas konsep dan interpretasi Aestethics of Misery, dalam paper ini juga dilakukan studi banding dengan fenomena dalam desain interior kontemporer. Metode analisis deskriptif dipakai untuk menjelaskan latar belakang dan tujuan. Observasi dalam desain interior dipakai sebagai interpretasi konsep ini sekaligus sebagai studi banding dengan konsep the Aesthetic of Misery. Tujuannya untuk menemukan implementasi bahwa sesuatu yang Andre Branzi dan Michele de Lucchi sebut sebagai Estetika Penderitaan dalam berbagai pendekatan dan gaya desain, telah ada dalam karya desain interior. Hasil penelitian menunjukkan bahwa dalam bentuk tidak langsung, konsep penderitaan dalam berbagai pendekatan dan gaya desain ada atau direpresentasikan dalam karya desain interior gaya industrial yang selain menggunakan material bernuansa pabrik tua, secara simbolik menunjukkan unsur penderitaan. Kata Kunci: estetika, estetika penderitaan, lingkungan sosial, desain interior